КАРЛ ПОППЕРНИНГ МЕТОДЛАР ТЎҒРИСИДАГИ ТАЪЛИМОТИ - Ҳотамов, А. (SCIENCE and SOCIETY, 2024)
This article analyzes the methodological concept of the philosopher K. Popper. The article covers the views of K. Popper on the unity and universality of the methods of natural and social sciences.
Keywords: method; methodology; induction; deduction; hypothesis; theory; natural sciences; social sciences; theoretical sciences; historical sciences; explanation; description